Theories in the Tradition of Dominant Paradigm Nutrition Communication and Education: Enhancing nutrition communication for a healthier India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India today is standing up to an odd conundrum of being home to a great many undernourished just as to a developing number of overweighthefty individuals. The quest for answers for tackle these issues had frequently pointed at nutrition communication as one of the important conditions. Given the maze of nutritional issues, various methodologies are being used and they are required to fill shifted needs, including mindfulness creation, limit building, strategy promotion, conduct and social change. For nutrition communication to be fruitful, numerous degrees of communication from assorted points of view should be at the same time initiated, with a dialogical commitment among the researchers and experts working at the distinctive open levels. Communication ought to be a principal segment of all nutrition programs with sufficient financial plan and fitting assessment instrument fused right at the arranging stage. Communicators ought to go past their institutional factors just as individual convictions to pick comes closer from a blend of models and practices to bridle from differed communication speculations and encounters from training.